Training Outcome Evaluation Model. (2016) - Moldovan, Liviu
Abstract: Kirkpatrick's model has many adaptations to various fields of training, by using 4 level evaluations. The new eQvet-us training outcome evaluation model developed in this paper, consist in an improvement of the Kirkpatrick's model by associating to the evaluation level the corresponding objectives. In this way two levels are deduced, that are following the PDCA cycle in opposite senses. The objectives' level consists in outcome, performance, knowledge, motivation, that is associated to the classical evaluation level compost of reaction, learning, behavior and result evaluations. To evaluate the effectiveness of the proposed approach, an experiment was conducted for a VET course for quality professionals in services industry. It was demonstrated that the methodology not only help the training professional plan the intervention, but help the trainees employers understand the factors that facilitate training transfer and produce business results. By using the tool, we have demonstrated post-training value for stakeholders.